2009
DOI: 10.1038/ijo.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity and high-risk fat: a longitudinal population-based twin study

Abstract: Background and Objective: Exercise is thought to reduce high-risk body fat, but intervention studies are frequently limited by short follow-ups and observational studies by genetic selection. Therefore, we studied the effects of a physically inactive vs active lifestyle on high-risk (visceral, liver and intramuscular) fat in twin pairs discordant for leisure-time physical activity habits for over 30 years. Design: A longitudinal population-based twin study. Subjects: Sixteen middle-aged (50-74 years) same-sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 50 publications
9
73
1
7
Order By: Relevance
“…However, use of BMI as a covariate is problematic as both high muscle mass and high fat mass can contribute to high BMI. Our previous twin studies have shown that despite the lack of statistically significant differences in BMI between physically active and inactive members of twin pairs, physical activity reduces waist [24] and high-risk body fat (ectopic fat stores, liver fat and visceral fat) but maintains skeletal muscle mass and function [33], leading to lowered type 2 diabetes risk independent of BMI. It is also possible that the results from BMI-adjusted analyses are overadjusted, as physical activity may reduce type 2 diabetes by independently reducing BMI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, use of BMI as a covariate is problematic as both high muscle mass and high fat mass can contribute to high BMI. Our previous twin studies have shown that despite the lack of statistically significant differences in BMI between physically active and inactive members of twin pairs, physical activity reduces waist [24] and high-risk body fat (ectopic fat stores, liver fat and visceral fat) but maintains skeletal muscle mass and function [33], leading to lowered type 2 diabetes risk independent of BMI. It is also possible that the results from BMI-adjusted analyses are overadjusted, as physical activity may reduce type 2 diabetes by independently reducing BMI.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, physical activity or exercise training has been shown to reduce visceral fat [33], improve skeletal muscle insulin sensitivity [37,38] and increase the oxidative capacity of skeletal muscle, which correlates with insulin sensitivity [39], and also leads to increased/modified fat oxidation, which is most likely to prevent lipid-mediated insulin resistance [40].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, exercise-induced retention of muscle strength rather than that of muscle mass could be the key factor in the maintenance of muscle function to avoid age-related mobility limitations (Hughes et al 2001;Visser et al 2005;Goodpaster et al 2006;Newman et al 2006;Delmonico et al 2009). Furthermore, regular physical activity is an effective way to slow down the age-and/or inactivity-related infiltration of muscle fat Delmonico et al 2009;Leskinen et al 2009b). However, the role of muscle fat infiltration in strength loss, muscle weakness, and mobility limitations needs further study (Visser et al 2005;Goodpaster et al 2008;Delmonico et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the accumulation of ectopic "high-risk" fat and adipocyte function are important mechanisms in mediating the prolonged effects of life-long regular exercise on glucose metabolism (Goodpaster et al 2000;Boule et al 2005;Petersen and Shulman 2006;Dube et al 2008;Leskinen et al 2009b;Taube et al 2009;Rector and Thyfault 2011). Notably, the cotwins did not differ significantly in either body weight or BMI (see Table 1), and there were no differences in their fat intakes (Rintala et al 2011), yet the inactive co-twins had significantly more visceral, intramuscular, and liver fat, as we have reported earlier (Leskinen et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…32 Intensive substudies of these physical activity discordant twins further revealed that although the physically inactive (79.5 ± 18.4 kg) and active twins (72.9 ± 11.9 kg) had only small differences in body weight, the inactive twins had 170% more liver fat and 54% more intramuscular fat than the active twins. 33 Thus, the value of physical activity should not be judged only by its' effects on body weight.…”
Section: Development Of Obesitymentioning
confidence: 99%